Exploring the Conformational Impact of Glycine Receptor TM1-2 Mutations Through Coarse-Grained Analysis and Atomistic Simulations - Mhashal, Anil Ranu; Yoluk, Ozge; Orellana, Laura (Frontiers in Molecular Biosciences, 2022)
Pentameric ligand-gated ion Channels (PLGICs) are a family of proteins that convert chemical signals into ion fluxes through cellular membranes. Their structures are highly conserved across all kingdoms from bacteria to eukaryotes. Beyond their classical roles in neurotransmission and neurological disorders, PLGICs have been recently related to cell proliferation and cancer. Here we focus on the best characterized eukaryotic channel, the Glycine Receptor (GlyR) to investigate the mutational patterns in genomic-wide screens of tumor cells and compare them with mutations linked to hyperekplexia, a mendelian neuromotor disease. Based on mutational clustering, conservation and phenotypic data, we select three novel GlyR mutations near the pore for an integrative computational study. Using the Principal Components from GlyR experimental structures as framework to track sampling by MD simulations, we explore the main motions involved in transitions between the open, closed and desensitized states and how they are perturbed by mutations. Our simulations reveal how WT GlyR spontaneously explores opening and re-sensitization pathways that, in the case of mutations, result in increased hydration of the pore.